LGBT Perspektif Hadis Nabi SAW - M. Asna Mafaza; Izza Royyani (STID Raudlatul Iman Sumenep, 2020)
The current issue on contemporary discussion is about LGBT (Lesbian, Gay, Bisexual and Transgender). LGBT is related to sexual behavior. it refers to a situation where the culprit has a sexual tendency that likes the same sex. There are a number of things that can cause symptoms that are inherited from birth and environmental factors. Their existence until now is certainly very difficult to be accepted among the public in general, because it is considered as a deviation and is contrary to the moral and religious values ​​that exist in society and not a few who blaspheme the perpetrators as perpetrators of major sins that need to be punished. Historically Islam, the LGBT phenomenon has existed since the time of the Prophet Lut, where his people have done very taboo acts, namely channeling sexual appetite to the same sex, their behavior is called ‘Sodom’. Islam strictly forbids this, as evidenced by the descent of the disaster to the people of the Prophet Luth.according to Islamic view of LGBT explicitly can be found in the explanation of the hadith. So, to understand this phenomenon, a study of the hadith in question is carried out. The study of this hadith was carried out as a basis for addressing the LGBT phenomenon that is rife in Indonesia. However, to implement the understanding of the hadith as a whole is certainly not easy to do, because Indonesia is not a country that makes Islam a state system. It has its own perspective regarding LGBT phenomena. Therefore, it is very important to have an in-depth study of the traditions that talk about LGBT so that this phenomenon can be seated and addressed as it should be, especially in the context of Indonesia which upholds human rights. Salah satu isu yang masih sangat hangat diperbincangkan dalam raung publik saat ini adalah isu tentang Lesbian, Gay, Biseksual dan Transgender.LGBT berkaitan dengan perilaku seksual.Ia mengacu kepada keadaan di mana pelakuknya memilki kecenderungan seksual yang menyukai sesama jenisnya. Ada beberapa hal yang dapat menyebabkan lgbt dianatanya pembawaan dari lahir dan faktor lingkungan. Eksistensi mereka hingga saat ini tentunya sangat sulit diterima di kalangan masyarakat secara umum, sebab dianggap sebagai sebuah penyimpangan dan bertentangan dengan nilai moral dan agama yang ada dalam masyarakat serta tidak sedikit yang menghujat pelakuknya sebagai pelaku dosa besar yang perlu dihukum.Secara historis Islam, fenomena LGBT telah ada sejak masa Nabi Luth, di mana kaumnya telah melakukan perbuatan yang sangat tabuh, yaitu menyalurkan nafsu seksual ke sesame jenis, perilaku mereka disebut sodom. Dan Islam dengan tegas melarang hal tersebut, terbukti dengan diturunkannya musibah kepada kaum Nabi Luth as.waktu itu. Pandangan Islam tentang LGBT ini secara eksplisit dapat ditemukan dalam penjelasan hadis Raslullah saw. Maka untuk memahami fenomena tersebut, dilakukan kajian terhadap hadis yang dimaksud.Kajian terhadap hadis ini dilakukan untuk menjadi dasar dalam menyikapi fenomena LGBT yang tengah marak di Indonesia.Namun, untuk menerapkan pemahaman hadis tersebut secara menyeluruh tentu tidak mudah dilakukan, sebab Indonesia bukanlah negara yang menjadikan Islam sebagai sistem dalam bernegara.Ia memiliki sudut pandangnya sendiri berkaitan dengan fenomena LGBT. Oleh sebab itu, sangat penting kiranya dilakukan kajian mendalam tentang hadis-hadis yang berbicara tentang LGBT agar fenomena ini bisa didudukkan dan diatasi sebagaimana mestinya, utamanya dalam konteks Indonesia yang sangat menjunjung hak-hak kemanusiaan.